COMPARATIVE ANALYSIS OF TEACHING METHODS SWIMMING (Web of Technology: Multidimensional Research Journal, 2024)
The article examines the methodological techniques and features of the educational process in swimming. The choice and application of a specific method in practice depends on a number of factors and conditions. It is shown that the authors use various methods of teaching swimming.